2021
DOI: 10.3390/ijms22041854
|View full text |Cite
|
Sign up to set email alerts
|

Wnt/β-catenin Pathway-Mediated PPARδ Expression during Embryonic Development Differentiation and Disease

Abstract: The Wnt/β-catenin signaling pathway plays a crucial role in early embryonic development. Wnt/β-catenin signaling is a major regulator of cell proliferation and keeps embryonic stem cells (ESCs) in the pluripotent state. Dysregulation of Wnt signaling in the early developmental stages causes several hereditary diseases that lead to embryonic abnormalities. Several other signaling molecules are directly or indirectly activated in response to Wnt/β-catenin stimulation. The crosstalk of these signaling factors eit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 53 publications
(124 reference statements)
0
15
0
Order By: Relevance
“…Instead, our findings indicate that NT promotes ISC function by up-regulating WNT/β-catenin signaling and Lgr5 mRNA expression in ISCs and progenitor cells. Because PPARδ is a WNT target, 67 it is plausible that the increase in PPARδ signaling during fasting observed by us and others 4 is a product of WNT/β-catenin activation. This is consistent with the observation that expression of Lgr5 mRNA and WNT target genes is up-regulated in the crypts of human ileum after prolonged absence of enteral nutrients, despite a reduction in total ISC numbers.…”
Section: Discussionmentioning
confidence: 88%
“…Instead, our findings indicate that NT promotes ISC function by up-regulating WNT/β-catenin signaling and Lgr5 mRNA expression in ISCs and progenitor cells. Because PPARδ is a WNT target, 67 it is plausible that the increase in PPARδ signaling during fasting observed by us and others 4 is a product of WNT/β-catenin activation. This is consistent with the observation that expression of Lgr5 mRNA and WNT target genes is up-regulated in the crypts of human ileum after prolonged absence of enteral nutrients, despite a reduction in total ISC numbers.…”
Section: Discussionmentioning
confidence: 88%
“…Wnt/β‐catenin signalling is a conserved development pathway, 33 and however, it is reactive in multiple kinds of kidney diseases. 34 Interestingly, we have found that it is also overactivated in aged kidneys.…”
Section: Discussionmentioning
confidence: 99%
“…The Wnt/ β -catenin pathway, as a highly conserved and tightly regulated signaling pathway, plays a crucial role in regulating embryonic development [ 63 ]. Its deregulation has been closely related to the occurrence of many malignancies, including breast and colon cancers.…”
Section: Lncrnas Mediating the Wnt/snail Signaling Pathwaymentioning
confidence: 99%